Environmental Specification of Pluripotent Stem Cell Derived Endothelial Cells Toward Arterial and Venous Subtypes - Arora, Seep; Yim, Evelyn K. F.; Toh, Yi-Chin (Frontiers in Bioengineering and Biotechnology, 2019)
Endothelial cell (EC) are required for a multitude of cardiovascular clinical applications, such as revascularization of ischemic tissues or endothelialization of tissue engineered grafts. Patient derived primary ECs are limited in number, have donor variabilities and their in vitro phenotypes and functions can deteriorate over time. This necessitates the exploration of alternative EC sources. Although there has been a recent surge in the use of pluripotent stem cell derived endothelial cells (PSC-ECs) for various cardiovascular clinical applications, current differentiation protocols yield a heterogeneous EC population, where their specification into arterial or venous subtypes is undefined. Since arterial and venous ECs are phenotypically and functionally different, inappropriate matching of exogenous ECs to host sites can potentially affect clinical efficacy, as exemplified by venous graft mismatch when placed into an arterial environment. Therefore, there is a need to design and employ environmental cues that can effectively modulate PSC-ECs into a more homogeneous arterial or venous phenotype for better adaptation to the host environment, which will in turn contribute to better application efficacy. In this review, we will first give an overview of the developmental and functional differences between arterial and venous ECs. This provides the foundation for our subsequent discussion on the different bioengineering strategies that have been investigated to varying extent in providing biochemical and biophysical environmental cues to mature PSC-ECs into arterial or venous subtypes. The ability to efficiently leverage on a combination of biochemical and biophysical environmental cues to modulate intrinsic arterio-venous specification programs in ECs will greatly facilitate future translational applications of PSC-ECs. Since the development and maintenance of arterial and venous ECs in vivo occur in disparate physio-chemical microenvironments, it is conceivable that the application of these environmental factors in customized combinations or magnitudes can be used to selectively mature PSC-ECs into an arterial or venous subtype.